Growth variation in the endangered fish Zingel asper: Contribution of substrate quality, hydraulics, prey abundance, and water temperature. Issue 7 (19th April 2022) - Monnet, Gauthier; Corse, Emmanuel; Archambaud‐Suard, Gaït; Grenier, Rémi; Chappaz, Rémi; Dubut, Vincent
Abstract: Intraspecific variation in life histories and its environmental correlates can indicate the degree of vulnerability to extinction of endangered taxa and guide conservation actions. Zingel asper (Percidae) is an endangered fish endemic to the Rhône catchment (France and Switzerland), where five populations subsist in separate river systems (Loue, Beaume, Durance, Verdon, and Doubs). Two populations of Z. asper differ in growth and longevity, but the existence of broader intraspecific differentiation in life histories and the environmental origins of this variation (if any) remain unknown. The age structure and growth profile of four populations of Z. asper (Loue, Beaume, Durance, and Verdon) and nine additional sub‐populations within the Durance system were determined by scale‐reading analysis, before evaluating the contribution of measured variation in substrate quality, hydraulics, prey availability, and water temperature to growth differentiation among and within populations. A trade‐off between early growth and longevity largely differentiated the populations of Z. asper along a slow (i.e. slower growth, smaller adult size, longevity of >5 years) to fast (i.e. faster growth, larger adult size, longevity of <4 years) continuum of life histories. This continuum differentiated populations from different river catchments along a south (Durance, Verdon) to north (Beaume, Loue) latitudinal gradient, and mapped onto an upstream–downstream gradient of sub‐populations within the Durance system. Differences in prey availability, hydraulics, and water temperature explained most of the growth variation among populations from different catchments, whereas local variation in prey availability, substrate quality, and water temperature mostly contributed to within‐river growth differentiation. These results indicate that short life cycles strongly expose all populations of Z. asper to extirpation and should motivate additional conservation actions. This study illustrates how quantifying intraspecific variation in life histories and its sensitivity to ecological context can reliably assess extinction risk and guide conservation actions by identifying endangered populations requiring priority management.